Knowledge, attitude and practice in burn first aid among nursing student at school of health sciences, Universiti Sains Malaysia - Munir, Muhammad Shafiq (Universiti Sains Malaysia, 2024)
Burn injuries represent a significant public health concern globally, with substantial impacts on morbidity, mortality, and quality of life. Despite advancements in burn injury knowledge and first aid protocols, a notable gap exists in understanding the practices and perceptions of burn first aid among nursing students. This study aims to determine the knowledge, attitudes, and practices (KAP) regarding burn first aid among nursing students at Universiti Sains Malaysia Health Campus. A cross-sectional study design was employed, involving 165 nursing students who were selected through convenience sampling. Data were collected using a structured questionnaire that assessed participants' knowledge, attitudes, and practices concerning burn first aid. The findings reveal that the mean knowledge score was 3.802, with 88 respondents (52.4%) demonstrating good knowledge of burn first aid. The mean attitude score was 3.464, with 83 respondents (49.4%) showing a favourable attitude, while the mean practice score was 0.652, with 83 respondents (49.4%) displaying poor practice. Descriptive analysis indicated that knowledge, attitudes, and practices varied among respondents, highlighting areas needing improvement. Association between sociodemographic and KAP was tested using Chi-square test showed significant associations between better knowledge and advanced years of study (p=0.021), degree-level education (p=0.046), and prior awareness of burn first aid (p=0.016). Degree students exhibited significantly better practices (p=0.017). However, age, participation in burn first aid training, timing of training, personal burn experience, and level of attitudes were not significantly influence knowledge or practice levels. The study concludes that addressing these educational gaps is crucial for improving overall burn care preparedness and outcomes. By ensuring timely and effective responses to burn incidents, the quality of patient care can be significantly enhanced.